Associations of hedonic and eudaimonic orientations with subjective experience and objective functioning in academic settings: The mediating roles of academic behavioral engagement and procrastination - Chen, Hezhi; Zeng, Zhijia (Frontiers in Psychology, 2022)
The question of how the pursuit of happiness affects an individual’s actual well-being has received much scholarly attention in recent years. However, few studies have investigated the associations of happiness orientation with people’s subjective experience and objective functioning simultaneously. The current research examines the possibility that hedonic and eudaimonic orientations have different relationships with college students’ affective well-being and academic achievement, while taking into consideration the behavioral mechanism that underlies the process. Data were collected with a final sample of 566 Chinese undergraduate students. The results confirmed that overall hedonic orientation was negatively associated with affective well-being and academic achievement, whereas eudaimonic orientation was positively associated with these outcomes. The study further found that both academic behavioral engagement and procrastination played mediating roles in the associations of happiness orientation with positive affect and academic achievement. However, only procrastination mediated the relationship between happiness orientation and negative affect. Theoretical and practical implications were discussed.